Usefulness of training camps at high altitude for well-trained adolescents - Jiří Suchý; Jakub Opočenský (Palacký University Olomouc, 2015)
Objective: Opinions on the suitability of sports training at altitudes of 1800-2200 m above sea level (ASL) for increasing performance in youth are not unanimous. The objective of this study was to test the influence of a ten day altitude training camp on performance in well-trained adolescent cross-country skiers. Methods: A running test of 3 × 2 km (aerobic, anaerobic and critical intensity) was used with a rest interval of 10 minutes. The test was performed 4 times - an initial test at a lowland (900 m ASL) prior to departure for altitude, two tests at altitude (1850 m ASL), a final test ten days after returning to lower altitudes. The aerobic, anaerobic and critical load intensities were set by graded a load test. For all individual tests, the participants maintained the same heart rate individually defined for the various segments using a heart rate monitor. Changes in speed between the tests were compared. The body's internal response was also monitored by the concentration of lactate (2 and 8 minutes after each exertion). Participants: Well-trained adolescent cross-country skiers (N = 11, age: 14.4 ± 1.2 years, weight: 54.4 ± 8.6 kg, height: 170 ± 7 cm, fat: 13 ± 2.6%). Results: The average times attained in the first altitude test for aerobic and anaerobic load were higher (p < .05) than in the entry test at low altitude. In the second altitude test the average times for all intensities were significantly (p < .05) higher than in the first altitude test. In the tests after returning to the lower altitudes the times attained for all intensities were on average higher than at altitude. The average lactate concentration levels following the various intensities were similar (p > .05). The dynamics of the cool-down monitored via the lactate value at the eighth minute after completing the relevant segment showed that at altitude the adolescents cooled down significantly (p < .05) slower rate following the aerobic and anaerobic intensity than at low altitude. For critical intensity there was no statistically significant (p < .05) change in the kinetics of cooling down measured by lactate concentration between altitude and the low altitudes. Conclusions: In the model we were testing, the ten day altitude camp was to verify a positive effect on adolescents in acute improvement of their performance ten days after their return to low altitude. Thus it is physiologically suitable for adolescents, as with adults, to include altitude training with the objective of a subsequent rise in performance at low altitude. In accordance with the principles of a long-term approach to sports training corresponding to development, however, we believe that the use of higher altitudes is unnecessary for adolescents.